Temperatura de incubação e estimativa da razão sexual de filhotes de Lepidochelys Olivacea (Eschscholtz, 1829) (Testudines, Cheloniidae), no Espírito Santo, Brasil - Vasconcelos, Daniele Giulianna de (2017)
Worldwide seven species of sea turtles are listed, divided into two families - Dermochelyidae and Cheloniidae, five of which occur in Brazil: Lepidochelys olivacea, Chelonia mydas, Eretmochelys imbricata, Caretta caretta and Dermochelys coriacea. Sea turtles are cosmopolitan reptiles, with migrations from hundreds to thousands of miles between feeding and spawning areas. Lepidochelys olivacea, known as the olive ridley turtle is the smallest of the sea turtles found in Brazilian waters. The state of Espírito Santo is considered a secondary nesting area for the species, because it presents a reduced number of spawnings. Marine chelonians present sexual determination depending on the temperature of the environment in which they are found. The sex ratio of these animals is directly related to the temperature of the soil and the incubation time of the nests, in which higher temperatures produce females, while the males are produced in mild temperatures. There is a sensitive period for the determination of sex, and this occurs around the middle third of incubation (20ºst to 41th day). A sex ratio of 1: 1 (50% male and 50% female) is produced when the embryos are exposed, in the second third of incubation, to the so-called pivotal temperature. The most common procedure for identifying sex in newborn chelonians is a histological analysis of the gonads, since the offspring do not have sexual dimorphism. Fieldwork was carried out on the northern coast of the municipality of Linhares, Espírito Santo, between the mouth of the river Doce, the village of Povoação and the spa of Pontal do Ipiranga in the breeding season of 2015/16. Through active search the nests of Lepidochelys olivacea were found and a temperature data logger was inserted to monitor the temperature during the whole incubation period and removed at the time of hatching of the cubs. We monitored the temperature of 15 nests of L. olivacea, which during the incubation period recorded temperatures between 29ºC and 32,5ºC. In the second third, the values were between 31°C, within the pivotal temperature for the study specie. The mean temperature of the nests with the mean temperature of the external environment were significantly different (p-value=0.000), and the mean temperature inside the nests (30.93°C) was higher than the external temperature (25.59°C). The mean number of male cub was significantly equal to the average number of female cub (pvalue=0.782). Analyzing the temperature with the days of incubation, it was evident that the higher the mean temperature of the nest, the lower the incubation time will tend to be. The number of nests, as well as the incubation time analyzed in previous seasons (between 2003/04 to 2015/16), since the temperature value is related to the days of incubation, we observed over the years 2003/04 to 2015/16 that the average number of days of incubation of the nests decreased over time and the mean reduction was higher in the PV base. We estimated sex ratio in 1: 1, with 50% females and 50% males in most of the nests studied, and the sexing of the pups also indicated no significant difference between the sexes.